Static and Dynamic Load Tests of Shaft and Base Grouted Concrete Piles - Jialin Zhou; Xin Zhang; Hongsheng Jiang; Chunhao Lyu; Erwin Oh (Advances in Civil Engineering)
This paper examines shaft and base grouted concrete piles by conducting vertical static load tests (SLTs) and dynamic load tests. Three concrete piles with shaft and base grouting, with base grouting only, and without grouting techniques were selected, and compressive SLTs were conducted. Two piles with grouting were also assessed with dynamic load tests. Another two uplift SLTs were conducted to one shaft and base grouted pile and one pile without grouting. Traditional presentations were provided to check whether the bored piles reached the design requirement. Interpretations of test results were also provided to determine the ultimate pile capacity. Results from these 5 SLT programs indicated that double-tangent and DeBeer's methods are close to each other, and Chin's method overestimates the pile capacity. Comparison of the results from the SLTs and dynamic load tests shows that the results from Chin's method are close to dynamic results, and Mazurkiewicz's method overestimates for friction resistance. The results also demonstrate that base and shaft grouted pile and base grouted pile increase by 9.82% and 2.89% in compressive capacity, respectively, and compared to the uplift SLTs; there is a 15.7% increment in pile capacity after using base and shaft grouting technology.